Farsi Hame-i DPs and Intensional Transitive Verbs - Alonso-Ovalle, Luis; Moghiseh, Esmail (Proceedings of the Amsterdam Colloquium, 2022)
Adverbial modification suggests that some, but not all, Intensional Transitive Verbs (ITVs) take clausal complements [11]. Evidence from Farsi, coming from the interpretation of hame-i DPs, confirms the split. Hame-i DPs are existential quantifiers that acquire universal force via exhaustification [6]. We provide new data showing that hame-i DPs can have free choice interpretations, but only under certain conditions. The pattern is new. Free choice interpretations of hame-i DPs are found with ITVs, but only those that do not seem to take clausal complements. ITVs that seem to take clausal complements pattern with modal auxiliaries, which don't allow for free choice readings. If free choice readings are derived when a modal expression intervenes between an exhaustivity operator, EXH, and the DP, this means that not all modal expressions can intervene between EXH and hame-i DPs. To account for the restricted availability of free choice interpretations, we propose that EXH and hame-i DPs need to be within the same minimal clause.